2015
DOI: 10.1155/2015/803705
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidative Stability of Baru (Dipteryx alataVogel) Oil Monitored by Fluorescence and Absorption Spectroscopy

Abstract: Baru (Dipteryx alata Vogel) is a native fruit of the Brazilian savanna that provides a nutritive oil, which also has medicinal properties. Baru fruits were collected in central-western Brazil, and the oil was obtained by pressing the seeds. The Baru oil was heated at 110 ∘ C for 24 h, and its oxidative stability was investigated by using fluorescence and absorption spectroscopy. The data showed that both absorption and fluorescence were able to precisely monitor the oil degradation induced by the thermooxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…Figure 4 shows the absorption increase at 232 and 270 nm as a function of heating time, confirming the formation of primary and secondary degradation products [16]. In addition, our results also shown ( Figure 5) that, for the pulp oil, the absorption at around 450 nm can be effectively used to monitor oil degradation by observing the carotenoid degradation [36] as recently demonstrated for baru (Dipteryxalata Vogel) oil [37]. In fact, the results demonstrated that carotenoid absorption exponentially decreases as a function of thermal degradation time guided by Equation (2):…”
Section: Optical Monitoring Of Oil Degradationsupporting
confidence: 82%
“…Figure 4 shows the absorption increase at 232 and 270 nm as a function of heating time, confirming the formation of primary and secondary degradation products [16]. In addition, our results also shown ( Figure 5) that, for the pulp oil, the absorption at around 450 nm can be effectively used to monitor oil degradation by observing the carotenoid degradation [36] as recently demonstrated for baru (Dipteryxalata Vogel) oil [37]. In fact, the results demonstrated that carotenoid absorption exponentially decreases as a function of thermal degradation time guided by Equation (2):…”
Section: Optical Monitoring Of Oil Degradationsupporting
confidence: 82%
“…To achieve significant enhancement of 1525 cm −1 mode, the wavelength of excitation laser should be close to the absorption edge of carotenoids. The absorption study showed that the absorption edge of carotenoids is about 510 nm [32]. Therefore, the intensity of the 1525 cm −1 mode would be strongly enhanced with excitation about 510 nm, and decrease with higher excitation wavelength.…”
Section: Resultsmentioning
confidence: 98%
“…The UV‐visible absorption and fluorescence results show that carotenoids and chlorophylls are the main natural pigments (chromophores and fluorophores) in the oil extracted from the fruits of B. cydoniifolia . It is well known that chlorophylls present two absorption bands, in the violet‐blue (350–450 nm) and red (650–700 nm) regions, while carotenoids absorb in the blue‐green (400–500 nm) range . Additionally, it is also well established that carotenoids and chlorophylls are responsible for emission in the 400–550 nm range and 650–750 nm range, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that chlorophylls present two absorption bands, in the violet-blue (350-450 nm) and red (650-700 nm) regions, while carotenoids absorb in the blue-green (400-500 nm) range. 35,36 Additionally, it is also well established that carotenoids and chlorophylls are responsible for emission in the 400-550 nm range and 650-750 nm range, respectively. 36,37 Furthermore, it is worth pointing out that both UV-visible absorption and fluorescence results revealed that the chlorophyll content decreased during the course of ripening, almost reduced to zero in the ripe oil.…”
Section: Color Of Oilsmentioning
confidence: 99%
See 1 more Smart Citation